The use of guided tissue regeneration in endodontic Microsurgery: Setting a threshold - Fatemah A. Alkandari; Mazen K. Alotaibi; Sami Al-Qahtani; Samhan Alajmi (Elsevier, 2024)
Aim: We aimed to compare the radiographic outcomes of conventional and regenerative approaches in endodontic microsurgery (EMS) and set a critical defect size for healing in conventional and regenerative therapies. Methodology: The study evaluated 53 root canal-treated teeth (33 patients) with periapical lesions. Among them, 19 teeth (35.8 %) were treated with regenerative treatment, whereas 34 teeth (64.1 %) were managed with the conventional approach. Conventional and regenerative approaches were performed by endodontic and periodontic residents under consultants' supervision. Healing was evaluated after a minimum period of 6 months by comparing pre- and post-operative cone-beam computed tomography (CBCT) findings. The radiographic interpretation was conducted by a single examiner who was not participating in the surgeries and was blind on the type of treatment prior to CBCT evaluation. New healing criteria were proposed owing to the limitations on the present criteria in evaluating endodontic surgery after regenerative treatment. Critical measurements were calculated for each approach based on periapical lesion dimensions. Results: The regenerative approach presented significantly better healing than conventional treatment (mean, 1.21 and 1.59, respectively; p = 0.047). Based on the critical-point calculations, the conventional approach was effective in lesions of up to 3 mm depth and height, whereas the regenerative approach resulted in better healing rates in lesions with 3-9 mm depth and 3-6 mm height. Conclusions: Performing the regenerative approach in EMS resulted in better healing rates than those of the conventional approach. The conventional approach is recommended for small periapical lesions, whereas the first had better results in larger lesions.